A Structured Approach for Assessing Sustainable Best Practices in Supply Chains - Piotrowicz, W; Cuthbertson, R (Springer Verlag, 2012)
This book chapter presents a structured approach to assess supply chain practices. The proposed solution incorporates sustainability dimensions into the evaluation process—considering social, economic and environmental impacts—and can be applied to select supply chain practices that can help to reduce the negative impact of transport, while improving long-term economic performance. Although there is no universal practice that can be applied across all business and national contexts, based on the extensive analysis of various supply chain practices across Europe, the most common ‘generic’ solutions used to improve supply chain are presented. The analysis of each ‘generic’ practice includes its social, economic and environmental impact, as well as its drivers and limitations, which should be considered when new implementation takes place.